2012
DOI: 10.1063/1.3688035
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of silicene fluoride and hydride

Abstract: Silicene is the graphene-like silicon nanosheet, which has been synthesized very recently [B. Lalmi, H. Oughaddou, H. Enriquez, A. Kara, S. Vizzini, B. Ealet, and B. Aufray, Appl. Phys. Lett. 97, 223109 (2010)]. Using first-principles calculations, we systematically investigate the structures and properties of fluorinated and hydrogenated silicene, the silicon analogues of graphane. Different from the carbon-counterpart, the fluorination prefers the conformation with a zigzag-line buckling, while the hydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
149
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 28 publications
13
149
1
2
Order By: Relevance
“…Due to strong spin-orbit coupling (SOC), the quantum spin Hall effect may be observed in silicene in an experimentally accessible temperature regime [13]. A tunable band gap can be opened up to about 4 eV in silicene by applying a perpendicular electric field [21][22] and by hydrogenation [23][24][25][26], halogenation [27][28], and oxidation [29][30]. Owing to these excellent properties and easy integration into the current Si-based semiconductor technology, silicene holds great promise for future applications in nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Due to strong spin-orbit coupling (SOC), the quantum spin Hall effect may be observed in silicene in an experimentally accessible temperature regime [13]. A tunable band gap can be opened up to about 4 eV in silicene by applying a perpendicular electric field [21][22] and by hydrogenation [23][24][25][26], halogenation [27][28], and oxidation [29][30]. Owing to these excellent properties and easy integration into the current Si-based semiconductor technology, silicene holds great promise for future applications in nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Silicene shares many important properties with graphene, especially the most fascinating one: the Dirac-type dispersions at the Fermi surface, which is shown by both first-principles calculations [7][8][9][10][11][12][13][14] and the measurements from different experiments. 1,3,4 Other than the similarity with graphene, silicene has its own advantages.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that fluorinated silicene is more stable than silicane and with a smaller bandgap. 52,55 Bromine was found to lead to even more interesting behavior. 59 Half-brominated silicene is an antiferromagnetic half-metal, whereby one spin channel is metallic, and the other is semiconducting with a 1.73 eV energy gap.…”
mentioning
confidence: 99%